Fluorescent Rosamine/TiO2 Composite Films for the Optical Detection of NO2. (29th March 2018) - Guillén, María G.; Suárez, Belén; Roales, Javier; Gámez, Francisco; Vargas, Alejandro P.; Moscoso, Francisco G.; Lopes-Costa, Tânia; Queirós, Carla; Silva, Ana M. G.; Pedrosa, José M.
Abstract : Two rosamine derivatives were used as fluorescent sensors for the detection of NO2, a toxic and oxidant gas whose presence in populated areas needs to be controlled. Both compounds shared the same molecular structure but had different peripheral substituents: a carboxylic acid and an amino group. Transparent nanocrystalline TiO2 films were prepared by screen printing and used as substrates, where the rosamines were incorporated by simple immersion into their respective solutions to form composite films. According to the molecular structures of the rosamines, the anchoring to the substrates was proposed to be by either covalent bonding and electrostatic interaction, or only electrostatic interaction, and was determined by the different substituents in each rosamine. Upon their exposure to increasing concentrations of NO2, both types of composite films showed intense and fast spectral changes, and the speed of response was related to the concentration of the gas. The anchoring mode and the electrophilic effect of the substituents determined the better sensing capability and the faster response shown by the carboxylic derivative in all cases.